Interface avançada para orientação geográfica - Diogo Miguel Raposo Soares (2017)
The magnetic compass is one of the most basic tools used for pedestrian navigation and orientation, it is used to give a precise direction to the users. With the fast development of smartphone use, the traditional compass was many times replaced by sensors and applications that emulate its behaviour and show a similar visual feedback to the users. By providing only a visual interface, the user is forced to look at the smart-phone, losing awareness of the obstacles in his path. Also, this type of interface is useless for blind or visually impaired people. The idea is to create an advanced multimedia interface which integrates the functions of a traditional compass with audio, haptic and vibrational feedback, that may provide a highly usable "eyes-free" interaction. This advanced multimedia interface will give a good perception of direction, while doing pedestrian navigation activities, and it will be as no intrusive as possible to the users senses, since they are essential to avoid obstacles and to be aware of danger in general. Innovative user feedback interfaces like wearable vibration devices and bone conduction audio are some of the possible interfaces to be used, as they give the ability to have an "eyes-free" interface that is usable by everyone and interacts with the users without disturbing all of the other senses. The preservation of the senses is important to avoid dangerous situations and even more for people who have to rely mostly in one of the senses to compensate the lack of another. To provide an interface that meets all the specications described above, different ways to interact and give feedback to the users will have to be studied and evaluated and then a selection of which ones would help solving the problem and the ones that are useful for the final solutionwill be done. Also, it is known that the calculation of heading can be affected by changes in the magnetic field near the magnetometer in our smartphones and this needs to be addressed in order to give trustworthy information to the users. This innovative device, in the author's opinion, will diminish the number of accidents of people, who get distracted from the rest of the world while using their smartphone. On the other hand, it will help disabled people, who otherwise were discriminated when a device is invented to fulfil everyone else's needs without thinking about their own needs in particular. Therefore, this is what makes this application stand out from what already exists.